2010
DOI: 10.1002/esp.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of grass strips in trapping suspended sediments from runoff

Abstract: Little information is available concerning the performance of grass strips for erosion control from steep cropland. An experiment was conducted on 5-m-long grass strips with slopes of 3°~15° that were subjected to silt laden runoff and simulated rainfall, to investigate the sediment trapping processes. The grass strips had three treatments including intact grass control (C), no litter (dead grass material covering the soil surface was removed) (NL), and no litter or leaves (only 2~3 cm grass stems and roots we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 28 publications
8
61
2
1
Order By: Relevance
“…및 38%가 제거되었다 (Dunn et al, 2011). 그 밖의 많은 연구 에서도 강변 완충대가 발휘하는 비점오염원 물질의 제거능이 밝혀진 바 있다 (Agouridis et al, 2005;Dahlin et al, 2005;Dorioz et al, 2006;Haycock and Pinay, 1993;Lee et al, 2003;Oteroa et al, 2011;Pan et al, 2008;Pan et al, 2010). 이러한 영양염류 제거 과정은 그것이 문화적 부영양화를 크게 줄일 수 있게 때문에 생태학적으로 중요하다.…”
Section: 하천을 따라 형성된 강변식생은 많은 동・식물의 중요한unclassified
“…및 38%가 제거되었다 (Dunn et al, 2011). 그 밖의 많은 연구 에서도 강변 완충대가 발휘하는 비점오염원 물질의 제거능이 밝혀진 바 있다 (Agouridis et al, 2005;Dahlin et al, 2005;Dorioz et al, 2006;Haycock and Pinay, 1993;Lee et al, 2003;Oteroa et al, 2011;Pan et al, 2008;Pan et al, 2010). 이러한 영양염류 제거 과정은 그것이 문화적 부영양화를 크게 줄일 수 있게 때문에 생태학적으로 중요하다.…”
Section: 하천을 따라 형성된 강변식생은 많은 동・식물의 중요한unclassified
“…only grass stems and roots. STE ranged from 42-69%; 41-72% and 37-59% for the C, NL and NLL treatments, respectively, and thus Pan et al (2010) concluded that grass litter and leaves had no significant influence on STE of the local grass. …”
Section: Grass Stripsmentioning
confidence: 93%
“…For example, hedges of switch grass and Vetiver (Vetiveria zizanioides (L.) Nash) caused backwater depths of up to 40 cm and trapped >90% of sediment coarser than 125 µm in areas of concentrated overland flow (Meyer et al, 1995). The effect of grass litter and leaves on ST was also studied on the Loess Plateau, China (Pan et al, 2010) where perennial local grazing grass, black rye (Loliumperenne L.) were tested on slopes of 3-15 0 applying three treatments: C-control with intact grass, NL-no litter i.e. without grass covering the soil surface and NLL -no litter or leaves i.e.…”
Section: Grass Stripsmentioning
confidence: 99%
See 2 more Smart Citations